EVALUATING THE IMPACT OF THE DIABETES MELLITUS STRATEGY FOR THE NATIONAL HEALTH SYSTEM: AN INTERRUPTED TIME SERIES ANALYSIS - González-Touya, Marta; Carmona, Rocío; Sarría-Santamera, Antonio (Healthcare, 2021)
Diabetes mellitus is a significant public health problem. Macrovascular complications (stroke, acute myocardial infarction (AMI) and lower limb amputations (LLAs) represent the leading cause of morbi-mortality in DM. This work aims to evaluate the impact of the approval of the Diabetes Mellitus Strategy of the National Health System (SDM-NHS) on hospitalizations for those macrovascular complications related to DM; (2) Methods: Interrupted time series applying segmented regression models (Negative Binomial) adjusted for seasonality to data from hospital discharge records with a primary or secondary diagnosis of DM (code 250 ICD9MC); (3) Results: Between 2001 and 2015, there have been 7,302,750 hospital discharges with a primary or secondary diagnosis of DM. After the approval of the SDM-NHS, all the indicators showed a downward trend, modifying the previous trend in the indicators of AMI and LLA. The indicators of stroke and AMI also showed an immediate reduction in their rates; (4) Conclusions: After the approval of the SDM-NHS, an improvement has been observed in all the indicators of macrovascular complications of DM evaluated, although it is difficult to establish a causal relationship between the strategy and the effects observed. Interrupted time series is applicable for evaluating the impact of interventions in public health when experimental designs are not possible.
Keywords: Type of access: Open Access; diabetes mellitus; comorbidity; health plan implementation; public policies evaluation; interrupted time series; predictive and preventive strategies